A rare case of proximal gastric outlet obstruction misdiagnosed as pancreatic invasive tumor, case report. (2020) - El-Helou, Etienne; Ghoussoub, Youssef; Husseini, Hikmat
Highlights: Bouveret's syndrome is a rare entity which takes part of the gallstone ileus entities. There are no standardized recommendations for workup and management, and there is a high chance of misdiagnosis. In front of its vague presentation, various differential diagnosis should be taken into consideration. The diagnosis is usually confirmed by CT scan, showing the fistula and Rigler's Triad. Surgery is most of the times the definitive treatment. Abstract: Introduction: This report is a case of proximal gastric outlet obstruction, misdiagnosed after esophagogastroduodenoscopy as invasive pancreatic malignancy. We report this case because of its rarity and to encourage physicians to take this etiology into consideration as part of differential diagnosis. Presentation of case: We present a case of 88 year-old lady presenting for 3 days history of post-prandial coffee ground vomiting associated with obstipation, misdiagnosed as pancreatic malignancy with duodenal invasion after outpatient gastroscopy. The proper diagnosis was confirmed by CT Scan which revealed the presence of large calculi with aerobilia and gastric stasis. Surgery done to extract two impacted large gallstone of 2 × 2 × 1 and 6 × 3.5 × 3 cm followed by cholecystectomy, closure of fistulae, gastrojejunsotomy and vagotomy. Discussion: Bouveret Syndrome is referred to as rare presentation of gastric outlet obstruction by passage of large gallstone through a fistula between the gallbladder and proximal gastrointestinal tract. It has a vague presentation, and can be misdiagnosed due to non-specific symptoms. The diagnosis is usually confirmed by a CT scan and it is treated surgically most of the time. Conclusion: Bouveret syndrome is a rare entity, and should be taken into consideration as a differential diagnosis in front of proximal gastric outlet obstruction.